The Influence of Brand Image and Customer Satisfaction on Customer Loyalty at Indomaret Retail Stores In Bandung City - Mulia, Rudi; Bahri, Ronny Samsul (International Journal Labs, 2025)
The modern retail sector in Indonesia is experiencing rapid growth, with Indomaret emerging as a leading minimarket chain. In a competitive landscape, building customer loyalty is crucial for sustainable business success. This research aims to analyze the influence of brand image and customer satisfaction on customer loyalty at Indomaret retail stores in Bandung City. The research employs a quantitative approach using survey methods with a structured questionnaire distributed to respondents who regularly shop at Indomaret. Data were analyzed using multiple regression techniques to examine both the direct and indirect effects of the variables. The results indicate that brand image has a significant positive impact on customer satisfaction and loyalty. Furthermore, customer satisfaction mediates the relationship between brand image and customer loyalty, showing that a strong brand image enhances satisfaction, which in turn increases loyalty. The findings highlight the importance of building and maintaining a positive brand image and providing high-quality customer experiences to strengthen long-term loyalty. This research contributes to the understanding of consumer behavior in the modern retail sector and provides practical implications for retail managers in developing effective marketing strategies.